Plant Chromosome Engineering Methods and Protocols - Birchler, James A.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2011)
With an increasing human population and a decreasing amount of arable land, creative improvements in agriculture will be a necessity in the coming decades to maintain or improve the standard of living. In Plant Chromosome Engineering: Methods and Protocols, expert researchers present techniques for the modification of crops and other plant species in order to achieve the goal of developing the much needed novel approaches to the production of food, feed, fuel, fiber, and pharmaceuticals. This volume examines vital topics such as transformation procedures, chromosome painting, production of engineered minichromosomes, gene targeting and mutagenesis, site specific integration, gene silencing, protein expression, chromosome sorting and analysis, protocols for generating chromosomal rearrangements, enhancer trapping, and means of studying chromosomes in vivo. As a part of the highly successful Methods in Molecular Biology™ series, the methodological chapters include brief introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and professional tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Plant Chromosome Engineering: Methods and Protocols highlights the spectrum of tools currently available for modifying plant genomes and chromosomes and provides the foundation for crucial future developments.
Recent Advances in Plant Transformation -- Engineering the Plastid Genome of Nicotiana sylvestris, a Diploid Model Species for Plastid Genetics -- Homologous Recombination in Plants: An Anti-Review -- Chromosome Painting for Plant Biotechnology -- Plant B Chromosomes -- Telomere Truncation in Plants -- Engineered Plant Minichromosomes -- Method for Bxb1-Mediated Site-Specific Integration In planta -- Targeted Mutagenesis in Arabidopsis Using Zinc Finger Nucleases -- Vectors and Methods for Hairpin RNA and Artificial microRNA-Mediated Gene Silencing in Plants -- Recombinant Protein Expression in Nicotiana -- Chromosome Analysis and Sorting Using Flow Cytometry -- Super-Stretched Pachytene Chromosomes for Plant Molecular Cytogenetic Mapping -- Cytological Dissection of the Triticeae Chromosomes by the Gametocidal System -- Development and Use of Oat-Maize Chromosome Additions and Radiation Hybrids -- Enhancer Trapping in Plants -- Chromatin Beacons: Global Sampling of Chromatin Physical Properties Using Chromatin Charting Lines -- Transposable Elements as Catalysts for Chromosome Rearrangements.
Keywords: Plant science; Botany; Plant genetics; Genetic engineering; Plant Sciences; Plant Genetics and Genomics; Genetic Engineering